Acute Toxicity of Daphnia magna Neonates Exposed to Single and Composite Mixtures of Four Emerging Contaminants - Pinos-Vélez, Verónica; Araujo, Giuliana S. [UNESP]; Moulatlet, Gabriel M.; Pérez-González, Andrés; Cipriani-Ávila, Isabel; Tripaldi, Piercosimo; Capparelli, Mariana V. (Springer Nature, 2023)
The effects of emerging contaminants on environmental health are of high concern, especially those potentially induced by mixtures. We assessed single and composite mixtures of triclosan (T), 17β-estradiol (E2), sulfamethoxazole (SMX), and nicotine (N) at various concentrations, on neonates of Daphnia magna. When used in single exposure, T and N induced high toxicity (100% immobility, each one), compared to SMX and E2 (2.5% and 10% immobility, respectively). When T, E2, SMX and N were in mixture, T had the highest contribution to the overall toxicity in mixture exposures. The N toxicity lowered when in a fourfold exposure (85% immobility in fourfold exposure). Due to the high toxicity of T and N, both alone and in the mixtures, our results can serve as a warning about the use of these substances and their release in the aquatic ecosystem.
Keywords: 17β-estradiol; Antagonistic effects; Nicotine; Sulfamethoxazole; Synergic effects; Triclosan